2x+12(2)=(x-2)2+16(2)

Simple and best practice solution for 2x+12(2)=(x-2)2+16(2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+12(2)=(x-2)2+16(2) equation:



2x+12(2)=(x-2)2+16(2)
We move all terms to the left:
2x+12(2)-((x-2)2+16(2))=0
We calculate terms in parentheses: -((x-2)2+162), so:
(x-2)2+162
We multiply parentheses
2x-4+162
We add all the numbers together, and all the variables
2x+158
Back to the equation:
-(2x+158)
We get rid of parentheses
2x-2x-158+122=0
We add all the numbers together, and all the variables
-36!=0
There is no solution for this equation

See similar equations:

| 3x/2-1=11 | | 3/10x-2x+4/5=3/5 | | 2(w+3)-5(w-1)=32 | | 0.4x-0.5x-1=1 | | 5/6t+2/3t=54 | | |2x+3|=4x-1 | | 1+9n=4n+6 | | 2x12=-4 | | 33+3r=12+2r | | 7=w/8 | | 1=p+0 | | 1/3(2x-4)=6 | | -38=x+(-27) | | 5(x+3)+2x=-6 | | 8x+12x=280 | | W(3n)=12n+2 | | 3x/2-1x=1 | | 5/3+3m/8=55/24 | | 8+2x=280 | | w(-8)=4X+5 | | 7b-b+14=5b+3b | | 6(n-2)^2=864 | | 6x+4=-11x | | 3x+2=4+x+(1+2x) | | 8(x)+6(2x)=280 | | 4(3+c)=c=c+4 | | 8(x)+6(x)=280 | | 1/5^x^2-8=5^4 | | 23x+17+18x-1=180 | | x/7-3=9/14 | | 4x=4+2x+4 | | -(-x)x=46 |

Equations solver categories